English Language Teaching Materials and Cross-Cultural Understanding: Are There Bridges or Divides? - Jayakaran Mukundan (TEFLIN, 2005)
Abstract: English Language Teaching (ELT) materials can contribute immensely to cross-cultural understanding in the emerging globalised and borderless world. This is because there are common denominators present when materials are used in the teaching of the language across borders. An attempt to teach a language, for instance, must also consider the ways or the contexts in which it is used. Thus language cannot be detached from culture. The textbook or coursebook has been